The legacy of Liverpool's forgotten synchrocyclotron. (1st August 2022) - Lea, Rob
Abstract : The University of Liverpool's synchrocyclotron helped define physics in the 20th century, yet little trace of it remains. Rob Lea looks into the history of this lost machine.